PENERAPAN EVIDENCE BASED NURSING DENGAN INTERVENSI KOMPRES HANGAT TERHADAP PENURUNAN DERAJAT SKALA FLEBITIS PADA PASIEN DI RUANG INTENSIVE CARE UNIT (ICU) RS BHAYANGKARA TK.I R SAID SUKANTO - Risma Dianty Kusuma Putri, (2022)
Intravenous therapy is the main therapy used in all patients in hospitals, and serves to correct or prevent body fluid imbalances in hospitalized patients (Imamah 2018). However, this intravenous therapy has complications when given in the long term. Complications that occur from this therapy are phlebitis. This phlebitis occurs due to trauma to the patient's vein during infusion, causing redness, swelling, and can even cause fever. One of the non-pharmacological therapies to overcome these complications is warm compresses. This warm compress can reduce the swelling, and redness. This study used interviews and direct nursing care for two patients with phlebitis. The instrument used to measure the degree of phlebitis is the Visual Infusion Phlebitis (VIP) Score. Result: there was a decrease in the degree of phlebitis scale in one of the patients who were given warm compress therapy from a scale of degree 2 to 0